2006
DOI: 10.1002/ajmg.b.30280
|View full text |Cite
|
Sign up to set email alerts
|

No association between VNTR polymorphisms of dopamine transporter gene and attention deficit hyperactivity disorder in Chinese children

Abstract: Dopamine transporter (DAT) gene is implicated in the pathogenesis of attention deficit hyperactivity disorder (ADHD). Previously a meta-analysis concluded no association between the variable-number-of-tandem-repeats (VNTR) polymorphisms of the DAT gene and ADHD. However, significant heterogeneity was present among studies and no conclusion can be drawn about the association in any single ethnicity given the small number of studies. There were also conflicting results in Chinese populations. We therefore perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…For the 3ЈUTR VNTR, independent data were available from 15 TDT Brookes et al 2006b;Curran et al 2001b;Feng et al 2005b;Galili-Weisstub and Segman 2003;Hebebrand et al 2006;Kim et al 2005b;Kustanovich et al 2004;Lim et al 2006;Maher et al 2002;Mick et al unpublished data;Todd et al 2001a;Waldman et al 1998) and 19 Case-Control/HHRR studies (Bakker et al 2005;Banoei et al 2008;Bobb et al 2005;Carrasco et al 2004;Cheuk et al 2006b;Cook et al 1995;Cornish et al 2005;Das and Mukhopadhyay 2007;Genro et al 2007;Hawi et al 2003;Jiang et al 1999;Kim et al 2006b;Kopeckova et al 2008;Langley et al 2005;Qian et al 2004;Simsek et al 2005;Smith et al 2003;Swanson et al 2000b;Wang et al 2008), with the 480-bp (or 10-repeat) allele designated as the "risk" allele. Results of this meta-analysis, shown in Fig.…”
Section: Dopamine Transporter Gene (Dat1)mentioning
confidence: 99%
“…For the 3ЈUTR VNTR, independent data were available from 15 TDT Brookes et al 2006b;Curran et al 2001b;Feng et al 2005b;Galili-Weisstub and Segman 2003;Hebebrand et al 2006;Kim et al 2005b;Kustanovich et al 2004;Lim et al 2006;Maher et al 2002;Mick et al unpublished data;Todd et al 2001a;Waldman et al 1998) and 19 Case-Control/HHRR studies (Bakker et al 2005;Banoei et al 2008;Bobb et al 2005;Carrasco et al 2004;Cheuk et al 2006b;Cook et al 1995;Cornish et al 2005;Das and Mukhopadhyay 2007;Genro et al 2007;Hawi et al 2003;Jiang et al 1999;Kim et al 2006b;Kopeckova et al 2008;Langley et al 2005;Qian et al 2004;Simsek et al 2005;Smith et al 2003;Swanson et al 2000b;Wang et al 2008), with the 480-bp (or 10-repeat) allele designated as the "risk" allele. Results of this meta-analysis, shown in Fig.…”
Section: Dopamine Transporter Gene (Dat1)mentioning
confidence: 99%
“…For example, a recent study has demonstrated an association of the 9/10 genotype with more severe symptoms of ADHD when compared to the 10/10 genotype [111], whilst others pinpoint association with susceptibility to ADHD with the presence of a 10 repeat allele in family transmission studies [112][113][114][115][116][117]. In contrast, some studies found no association between DAT1 polymorphisms and ADHD using either family based [118,119] or population based studies [120,121]. However, a role for the DAT1 transporter in ADHD is strongly supported by the facts that DAT1 knockout mice are extremely hyperactive [122] and that current therapies for ADHD include drugs that act on the transporter e.g., methylphenidate (Ritalin).…”
Section: -Htt Variants and Anti-depressant Efficacymentioning
confidence: 99%
“…However, findings are heterogeneous and may depend on the specific statistical analysis method (Todd et al, 2005;Li et al, 2006;Yang et al, 2007;Langley et al, 2005;Cheuk et al, 2006). Furthermore, in adult samples, the nine-repeat allele has been shown to be associated with the disease, suggesting a differential association depending on age, and a role of SLC6A3 in modulating the ADHD phenotype over life time (Franke et al, 2008(Franke et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%